Neutrophil gelatinase-associated lipocalin prior to cardiac surgery predicts acute kidney injury and mortality. Issue 4 (9th August 2017) - Bulluck, Heerajnarain; Maiti, Raju; Chakraborty, Bibhas; Candilio, Luciano; Clayton, Tim; Evans, Richard; Jenkins, David P; Kolvekar, Shyam; Kunst, Gudrun; Laing, Christopher; Nicholas, Jennifer; Pepper, John; et al.
Abstract : Objective: We aimed to investigate whether preoperative serum neutrophil gelatinase-associated lipocalin (sNGALpre-op ) predicted postoperative acute kidney injury (AKI) during hospitalisation and 1-year cardiovascular and all-cause mortality following adult cardiac surgery. Methods: This study was a post hoc analysis of the Effect of Remote Ischemic Preconditioning on Clinical Outcomes in Patient Undergoing Coronary Artery Bypass Graft Surgery trial involving adult patients undergoing coronary artery bypass graft. Postoperative AKI within 72 hours was defined using the International Kidney Disease: Improving Global Outcomes classification. Results: 1371 out of 1612 patients had data on sNGALpre-op . The overall 1-year cardiovascular and all-cause mortality was 5.2% (71/1371) and 7.7% (105/1371), respectively. There was an observed increase in the incidence of AKI from the first to the third tertile of sNGALpre-op (30.5%, 41.5% and 45.9%, respectively, p<0.001). There was also an increase in both cardiovascular and all-cause mortality from the first to the third tertile of sNGALpre-op, linear trend test with adjusted p=0.018 and p=0.013,  respectively. The adjusted HRs for those in the second and third tertiles of sNGALpre-op compared with the first tertile were 1.60 (95% CI 0.78 to 3.25) and 2.22 (95% CI 1.13 to 4.35) for cardiovascular mortality, and 1.25 (95% CI 0.71 to 2.22) and 1.91 (95% CI 1.13 to 3.25) for all-cause mortality at 1 year. Conclusion: In a cohort of high-risk adult patients undergoing cardiac surgery, there was an increase in postoperative AKI and 1-year mortality from the first to the third tertile of preoperative serum NGAL. Those in the last tertile (>220 ng/L) had an estimated twofold increase risk of cardiovascular and all-cause mortality at 1 year. Clinical trial registration: NCT101247545; Post-results.